Giant Reed (Arundo donax): Biology, Identification and Management - Kurt Vollmer; Curtis Rainbolt; Jason Ferrell (EDIS)
SS-AGR-301, a 4-page illustrated fact sheet by Kurt Vollmer, Curtis Rainbolt, and Jason Ferrell, describes this tall perennial grass that is commercially grown in the Mediterranean to make reeds for musical instruments, and which is a major invasive weed in California and Texas watersheds — its biology, identification and management. Includes references. Published by the UF Department of Agronomy, March 2008.